2020
DOI: 10.1055/s-0040-1713375
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Inhibition with Ticagrelor versus Clopidogrel in Diabetic Patients after Percutaneous Coronary Intervention for Chronic Coronary Syndromes

Abstract: Background Clopidogrel is currently the only P2Y12 inhibitor with class I recommendation in patients after percutaneous coronary intervention (PCI) for chronic coronary syndromes (CCS). Diabetic patients have reduced therapeutic response to clopidogrel. Purpose This study assessed the antiplatelet effect of ticagrelor versus clopidogrel in diabetic patients after recent PCI for CCS. Methods Eligible patients were randomly assigned to receive ticagrelor 90 mg twice daily or clopidogrel 75 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…Contrary to our findings, no statistically significant difference was observed in the rates of life-threatening bleeding between the ticagrelor and clopidogrel group in the study done by Kumar and his team [15]. Another study done on diabetic patients after elective PCI for SCAD showed that ticagrelor was not associated with major bleeding [16], probably due to its advantage of being a reversible P2Y12 receptor inhibitor [17]. In the follow-up period during maintenance therapy, dyspnea was significantly reported in ticagrelor-treated patients than clopidogrel.…”
Section: Results Of Pharmacodynamic Studycontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, no statistically significant difference was observed in the rates of life-threatening bleeding between the ticagrelor and clopidogrel group in the study done by Kumar and his team [15]. Another study done on diabetic patients after elective PCI for SCAD showed that ticagrelor was not associated with major bleeding [16], probably due to its advantage of being a reversible P2Y12 receptor inhibitor [17]. In the follow-up period during maintenance therapy, dyspnea was significantly reported in ticagrelor-treated patients than clopidogrel.…”
Section: Results Of Pharmacodynamic Studycontrasting
confidence: 99%
“…They also suggested the presence of an anti-inflammatory effect for ticagrelor [24]. Previous research showed that after elective PCI for SCAD in diabetic patients, ticagrelor achieved a greater antiplatelet effect than clopidogrel [16]. The present study also showed the presence of inter-individual variability in clopidogrel concentration and revealed that Cmax levels obtained 2-3 hours after a loading dose of 600mg clopidogrel were variable between the patients.…”
Section: Results Of Pharmacodynamic Studysupporting
confidence: 71%
“…A number of studies have explained the reasons for platelet reactivity to clopidogrel, and include various genetic polymorphisms, hyporeactivity and drug interactions [3] . However, little information is available on the causes of ticagrelor resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the effect on platelet function of ticagrelor and clopidogrel in Chinese patients agreed with the ndings reported in Western populations. Although there have been several studies investigating the pharmacology and bleeding risk associated with two anti-platelet drugs among Asian populations [31][32][33][34], few studies have concentrated on their different effects on platelet function in such populations, using different PFTs including LTA and VASP test, even though only Verify Now was applied to evaluate the platelet inhibition with ticagrelor versus clopidogrel in diabetic patients after PCI in the study of Zhenyu Liu et al [35] Various kinds of PFT have been applied to monitor platelet activity in the setting of DAPT (aspirin and clopidogrel or ticagrelor) in large clinical trials. Verify Now, LTA, MEA and ow cytometry are most intensively used among those techniques.…”
Section: Discussionmentioning
confidence: 99%